Pengembangan Media Kartu “ADA BAKAD” dalam Meningkatkan Adaptasi Budaya Akademik pada Mahasiswa Baru - Nuha , Moch. Syihabudin; Cholil (Program Studi Bimbingan dan Konseling Islam, 2023)
This research is a model for the development of card media in improving academic culture adaptation in new students for the 2022/2023 academic year. This study aims to make new students understand the culture of campus culture and be able to adapt to their new environment, namely in the college environment. This research and development approach was conducted in eight main stages, namely: (1) Analyzing potential problems found in the field. (2) Collect information that supports the process and problem-solving using questionnaires, observations and interviews. (3) Preliminary design of the product, in this case it is ADA BAKAD card media with quartet card type. (4) Validation of product design by an expert test team, namely lecturers of the Islamic Guidance and Counseling Study Program UIN Sunan Ampel Surabaya with an average final calculation of 58 and 64 The value is included in the low and medium categories (5) Design improvements that have been given by the expert test team so that the product is of high quality and understood. (6) Product trials on field subjects and increased by 84 and 78. The result from the provision of interventions and pretest and posttest questionnaires, there was a change in the final value that increased by using ADA BAKAD